Optimalisasi Sistem Kerja dan Sumber Daya Manusia Laundry pada RPK Omah Laundry Prapen - Enoch David Lontolawa; Zumrotul Fitriyah (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2025)
This study examines a comprehensive approach to addressing common issues in laundry services, such as ineffective scheduling, skills gaps, and operational inefficiencies. The research focuses on RPK Omah Laundry Prapen, aiming to improve work processes and optimize human resources in this laundry business. The proposed solutions include the implementation of an attendance system, financial application training, laundry and ironing skills training, and a single-shift work system. The attendance system is designed to improve workforce punctuality, while the financial application training aims to enhance employees' understanding of financial management. Additionally, providing specific training on laundry and ironing techniques helps to bridge the skills gap and ensure high-quality service. The introduction of a single-shift work system aims to increase efficiency by streamlining operations and reducing staff fatigue. The results of the study indicate that these proposed solutions lead to several positive outcomes. The attendance system contributes to better time management, fostering a sense of responsibility among employees. Financial application training helps staff manage the business's finances more effectively, leading to more informed decision-making. Furthermore, the skills training program has shown improvements in the quality of laundry and ironing services, which directly impacts customer satisfaction and retention. The adoption of a single-shift work system reduces operational costs and increases the overall efficiency of the laundry services. Ultimately, this approach enhances fairness, operational efficiency, and productivity, creating a more conducive work environment. Implementing these integrated solutions can help laundries, such as RPK Omah Laundry Prapen, achieve better, sustainable performance by addressing key operational challenges and maximizing their workforce's potential. This study provides valuable insights for other laundries looking to optimize their operations and improve long-term business success.